Specific Roles of MicroRNAs in Their Interactions with Environmental Factors - Juan Wang; Qinghua Cui (Journal of Nucleic Acids)
MicroRNAs (miRNAs) have emerged as critical regulators of gene expression by modulating numerous target mRNAs expression at posttranscriptional level. Extensive studies have shown that miRNAs are critical in various important biological processes, including cell growth, proliferation, differentiation, development, and apoptosis. In terms of their importance, miRNA dysfunction has been associated with a broad range of diseases. Increased number of studies have shown that miRNAs can functionally interact with a wide spectrum of environmental factors (EFs) including drugs, industrial materials, virus and bacterial pathogens, cigarette smoking, alcohol, nutrition, sleep, exercise, stress, and radiation. More importantly, the interactions between miRNAs and EFs have been shown to play critical roles in determining abnormal phenotypes and diseases. In this paper, we propose an outline of the current knowledge about specific roles of miRNAs in their interactions with various EFs and analyze the literatures detailing miRNAs-EFs interactions in the context of various of diseases.